PERKEMBANGAN PENDIDIKAN ISLAM PADA MASA DAULAH FATIMIYAH (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2002)
When Abbasids conquered Ummayads of Baghdad in 132 H/750 M, the Syiah had supported the movement expecting to be rewarded with compensation and protection. The Syiah did such action because the Authority had continually pursued the fled of the Syiah to North Africa whose people coincidentally disinclined the Baghdad Governemtn who had burdened them with enormous taxes. In the period of 288 H-901H, led by Abdu Abdillah Asy Syi'i, the Syiah had finally succeed in establishing Bani Fatimiyali Government upon conquering the Bani Aghlab of Tunisia in advance. Fatimids had been desperately trying to conquer Egypt many times, but to no avail. It was only after Al Mu'iz Lidinillah held the power in 341-365 H (952-975 M) that the effort was finally succeed. They then moved the central government from Tunisia to Egypt and followed immadiately by the foundation of Jami' Al Azhar functioning as a place for developing the Syiah Ideology and preparing its bureaucrat cadres. By th time the Bani Fatimiyah, who held the power in 567-1171 M, was collapsed by Bany Ayyubiyah, from then on the Jami' Al Azhar Education Method had been shifted from Syiah Ideology to Sunny Ideology